EFEKTIVITAS INSENTIF PROMOSI (DISKON FLASH SALE, CASHBACK, DAN GRATIS ONGKIR) DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA PLATFORM E-COMMERCE SHOPEE - Ni Kadek Sioaji Yamawati; I Gde Agung Wira Pertama; I Gusti Ayu Ratih Permata Dewi; Rizqi Ardian Supriyanto (Warmadewa Management and Business Journal (WMBJ), 2025)
This study focuses on consumer behaviour dynamics in the e-commerce ecosystem, particularly on the Shopee platform. Initial observations indicate that many consumers, especially millennials, cancel their purchase intentions when they do not receive promotional incentives such as cashback, flash sale discounts, and free shipping. Barriers such as shipping costs, full prices without discounts, and the absence of cashback significantly influence purchasing decisions. The primary objective of this study is to empirically test and prove the influence of these three independent variables on the purchasing interest of millennial consumers in Denpasar. A quantitative approach was used, relying on primary data collected through questionnaires, as well as secondary data from relevant academic literature. The research population consisted of all millennials residing in Denpasar. Using purposive sampling, 97 respondents were selected as the research sample. The collected data were analysed using SPSS 25.0 for Windows with a series of statistical analysis techniques, including classical assumption tests, multiple linear regression analysis, F-tests, and t-tests. The analysis results show that cashback, flash sale discounts, and free shipping have a positive and significant influence on purchasing interest, both simultaneously and partially. These findings confirm the crucial role of promotional incentives in driving purchasing decisions and provide important strategic implications for marketers and e-commerce platform managers in designing effective promotional programmes.